1988
DOI: 10.3109/02844318809097938
|View full text |Cite
|
Sign up to set email alerts
|

Facial Skeletal Dimensions in Patients with Nasal Septal Deviation

Abstract: The anatomy and the concomitant function of the face seem to be reciprocal issues. Previous studies have shown that stenosis in the posterior part of the nose, hampering nasal air flow, is associated with a retrognathic face and a posterior rotation of the lower jaw, i.e. components of the adenoid syndrome. The present study examines facial cephalometric morphology in adults with a deviated nasal septal cartilage, i.e. an anteriorly positioned nasal stenosis. Compared to a group of unafflicted individuals, als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 14 publications
0
33
0
1
Order By: Relevance
“…Grymer et al (1991) examined 42 identical twins and found some influence of the nasal septum and total nasal resistance on the development of the nasomaxillary complex. Freng et al (1988) compared the facial growth in deviated and non-deviated septum patients and revealed significant growth problems in surrounding skeletal areas, such as smaller posterior facial height, which causes cartilage buckling, leading to resistance to normal nasal airflow. It seems that the cause of a congenital crooked nose may be part of a larger genetic problem.…”
Section: Discussionmentioning
confidence: 98%
“…Grymer et al (1991) examined 42 identical twins and found some influence of the nasal septum and total nasal resistance on the development of the nasomaxillary complex. Freng et al (1988) compared the facial growth in deviated and non-deviated septum patients and revealed significant growth problems in surrounding skeletal areas, such as smaller posterior facial height, which causes cartilage buckling, leading to resistance to normal nasal airflow. It seems that the cause of a congenital crooked nose may be part of a larger genetic problem.…”
Section: Discussionmentioning
confidence: 98%
“…reduced facial prognathism in the former but without addressing causality. Freng et al (1988) found reduced nasal height in NSD, and interpret this as indicating that an undersized bony framework was responsible for the buckling of the growing septum. D' Ascanio et al (2010) report increased facial height in NSD, and ascribe it to the effects of mouth-breathing.…”
Section: Discussionmentioning
confidence: 87%
“…It might be suggested that traumatic damage to the nasal septum, causing its deviation, may have led to anomalies in development of surrounding bony structures resulting in reduced facial height, especially as experimental evidence largely appears to support the notion of a direct relationship between nasal septal and anterior midfacial growth (discussion in Holton et al, 2011b). This is the implication of the interpretation made by Freng et al (1988) when they observed an association between NSD and reduced nasal height in modern subjects. Although trauma that did not result in fracture would not be detectable, if trauma to the nasal region was a frequent occurrence in the Wharram Percy population, then one would expect that, at least on occasion, it would have resulted in fracture.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations